A preliminary study on the prognostic significance of cysteine-rich EGF ligand domain 2 protein (CRELD2) in patients with triple negative breast cancer - Mehmet Zahid Kocak; Murat Araz; Siddika Findik; Aykut Demirkiran; Mustafa Korkmaz; Melek Karakurt Eryilmaz; Mehmet Artac (Biomolecules & Biomedicine)
The cysteine-rich epidermal growth factor ligand domain 2 protein (CRELD2) is associated with pathways that regulate epithelial-to-mesenchymal transition, a critical process driving cancer metastasis. This study aimed to determine the prognostic value of CRELD2 status on survival outcomes in triple-negative breast cancer (TNBC). Seventy patients were included in the study. Thirty-four patients were metastatic, and 36 patients were non-metastatic. CRELD2 protein expression in tumor tissue was determined by immunohistochemical staining (IHC). The patients were divided into two groups: CRELD2 positive and negative groups. Clinicopathological features and survival outcomes were compared between the groups. In the survival analysis of the non-metastatic patient group, five-year overall survival (OS) rate was 91.7% in the CRELD2-positive patient group and 91% in the negative group (P = 0.91). Median progression free survival (PFS) was 9.4 (95% confidence interval [CI]: 6.4–12.4) months in the CRELD2-positive group and 11.9 (95% CI: 8.2–18.6) months in the CRELD2-negative group (P = 0.04). The median OS was 17.2 (95% CI: 13.7–22.3) months in the CRELD2-positive group and 24.7 (95% CI: 21.8–29.6) months in the CRELD2-negative group (P = 0.02). In multivariate analysis, CRELD2 status (negative vs positive) (hazard ratio [HR]: 0.50, 95% CI: 0.38–0.96, P = 0.02) was determined to be a risk factor for OS and CRELD2 status (negative vs positive) (HR: 0.82, 95% CI: 0.33–0.96, P = 0.01) was defined as a risk factor for PFS in patients with metastatic TNBC. This is the first clinical study to determine the effect of CRELD2 on survival and as a prognostic marker in patients with triple metastatic breast cancer. These results need to be validated prospectively with a large sample size.